Harmonizing Islam, Culture, and Science Education: Efforts to Prevent the Secularization of Religious and General Knowledge - Mansir, Firman; Wadham, Ben; Busahdiar, Busahdiar; Farihen, Farihen; Ikhsan, Muh (Mimbar Agama Budaya, 2024)
This study aimed to elucidate the Islamic religious values present in science education in schools. Islamic Education (PAI) serves as a benchmark in every aspect of education in schools, particularly regarding the morality of students. Furthermore, Islamic Education is consistently juxtaposed with various other subjects, with the hope that the subjects accompanying it can impart positive values to the students. The research methodology employed was a qualitative approach using a literature review. Descriptive content analysis was utilized to analyze the data, enabling the results to address the research questions. The findings indicate that Islamic values in science education can provide a paradigm regarding the holistic concept of human beings and instill the importance of morality in every learning process for students. Therefore, Islamic content and science education can coexist to achieve good learning quality and cultivate morally upright and virtuous students.